Differential Risk of Incident Fractures Depending on Intensity and Frequency of Physical Activity According to Cognitive Status: A Nationwide Longitudinal Study - Kang, Dong Woo; Wang, Sheng-Min; Um, Yoo Hyun; Na, Hae-Ran; Kim, Nak-Young; Han, Kyungdo; Lee, Chang Uk; Lim, Hyun Kook (Frontiers in Medicine, 2020)
Background: Previous studies have demonstrated an increased risk of fractures in subjects with various degrees of cognitive impairments. Recently, there has been growing recognition of the vital effect of physical activity (PA) on delay and prevention of fractures in older adults. Objectives: This study aimed to evaluate the optimal intensity and frequency of PA needed to prevent fractures in cognitively preserved older adults (CP), participants with subjective cognitive decline (SCD), and dementia patients using a large-scale nationwide cohort study. Methods: Data from a nationwide health screening program for individuals at the transitional age of 66 years were used in this study. A total of 968,240 subjects was enrolled, followed from 2007 to 2014, and classified as CP (n=759874), SCD (n=195365), or dementia group (n=13001). Adjusted hazard ratios (aHRs) by demographic and known risk factors for fractures were evaluated to identify the impact of various frequency and intensity PA on the occurrence of hip, vertebral, and limb fractures. Results: In CP participants, the most noticeable reduction of hip and vertebral fracture risk was shown in those performing vigorous-intensity PA at least three times per week. In the SCD group, the risk decrement in hip and vertebral fractures was most prominent in subjects who performed multiple-intensity PAs at least three times a week regardless of intensity. In the dementia group, only high-frequency walking and high-frequency & multiple-intensity PA decreased the risk of hip fractures compared with absence of PA. Conclusion: These findings suggest a role for various PA intensity and frequency levels to prevent hip and vertebral fractures according to cognitive status. Further study is needed to validate the effects of PA intensity and frequency proposed in this study on fractures according to cognitive status.